Adverse consequences of access to individuals' information: an analysis of perceptions and the scope of organisational influence. Issue 6 (1st November 2017) - Karwatzki, Sabrina; Trenz, Manuel; Tuunainen, Virpi Kristiina; Veit, Daniel
Abstract: Organisations are highly interested in collecting and analysing customer data to enhance their service offerings and customer interaction. However, individuals increasingly fear how such practices may negatively affect them. Although previous studies have investigated individuals' concerns about information privacy practices, the adverse consequences people associate with external actors accessing their personal information remain unclear. To mitigate customers' fears, organisations need to know which adverse consequences individuals are afraid of and how to address those negative perceptions. To investigate this topic, we conducted 22 focus groups with 119 participants. We developed a comprehensive conceptualisation and categorisation of individuals' perceived adverse consequences of access to their information that includes seven types of consequences: psychological, social, career-related, physical, resource-related, prosecution-related, and freedom-related. Although individuals may limit their interactions with an organisation owing to consequences they associate with both the organisation and other actors, organisations can apply preventive and corrective mechanisms to mitigate some of these negative perceptions. However, organisations' scope of influence is limited and some fears may be mitigated only by individuals themselves or government regulation, if at all.